2016
DOI: 10.1111/j.1548-2456.2016.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, Violence, and Corruption: Perspectives from Mexico and Central America

Abstract: Robert J. Bunker, ed., Criminal Insurgencies in Mexico and the Americas: The Gangs and Cartels Wage War. New York: Routledge, 2013. Tables, figures, index, 210 pp.; hardcover $160, paperback $56.95. Robert J. Bunker and John P. Sullivan, Studies in Gangs and Cartels. New York: Routledge, 2014. Tables, figures, index, 232 pp.; hardcover $168, paperback $54.95. Michael Deibert, In the Shadow of Saint Death: The Gulf Cartel and the Price of America's Drug War in Mexico. Guilford: Lyons Press, 2014. Map, bibliogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…In relation to these five popular substances, Google Trends analyses for the period from the start of 2012 to the end of 2016 (Figure 2) showed that surface web users of highest attentiveness (interest) were from (descending order); US, Chile, Canada, Australia, Costa Rica, Uruguay, Puerto Rico, New Zealand, Argentina, and the UK. Apparently, several countries are from Latin and Central America; these were not compatible with the data retrieved from the darknet snapshot; this difference may be attributed to the traditional trade rather than e-trade of NPS in South and Central America (Atkinson et al, 2017;Duddley, 2010;Scott and Marshall, 1998;and Wolf, 2016). Additionally, Vol.…”
Section: Resultsmentioning
confidence: 79%
“…In relation to these five popular substances, Google Trends analyses for the period from the start of 2012 to the end of 2016 (Figure 2) showed that surface web users of highest attentiveness (interest) were from (descending order); US, Chile, Canada, Australia, Costa Rica, Uruguay, Puerto Rico, New Zealand, Argentina, and the UK. Apparently, several countries are from Latin and Central America; these were not compatible with the data retrieved from the darknet snapshot; this difference may be attributed to the traditional trade rather than e-trade of NPS in South and Central America (Atkinson et al, 2017;Duddley, 2010;Scott and Marshall, 1998;and Wolf, 2016). Additionally, Vol.…”
Section: Resultsmentioning
confidence: 79%
“…For example, to justify the hardline anti-gang policy, called Mano Dura, that it adopted in 2003, el Salvador's Nationalist Republican Alliance Party (ARENA) 'exploited public anxiety about crime by depicting gangs as the main source of citizens' insecurity,' even though these gangs inflicted the most harm outside of the communities that comprised ARENA's so-called electoral 'base' (Wolf 2016, 51). Notably these gangs were popularly linked to return migration form the US (Coutin 2007;Wolf 2016). It is not hard to envision political parties in countries such as Pakistan, India, Lebanon, and Kenya, to name a few examples, similarly linking diverse aspects of migrant transnationalism to their use of violence for political gain.…”
Section: State and Political Responses To Migrant Transnationalism Inmentioning
confidence: 99%
“…Además de lo anterior y de acuerdo con los análisis de las múltiples dimensiones de los indicadores de la paz positiva y negativa (Institute for Economic & Peace, 2016), se ha observado que en la medida en que los indicadores de paz positiva son mejores, los niveles de corrupción son menores, y el PIB por habitante es mayor; en contraste, el índice de paz negativa está relacionado con un incremento de la corrupción y una disminución del PIB. En otras palabras, la paz y la corrupción son dos asuntos que van de la mano y que deben ser analizados no solo desde la perspectiva de los expertos, sino desde los discursos que se tejen entre las personas comunes (Wolf, 2016). Pues si bien los indicadores objetivos de la corrupción caracterizan los países y sus prácticas cotidianas, las creencias y significados que las personas tienen sobre ello también muestran una fuerte relación con su conducta, tanto para ejecutar acciones corruptas como para reaccionar ante ellas (Persson, Rothstein y Teorell, 2013).…”
Section: El Contexto De Este Estudiounclassified